Intelligent System to Find the Health Care Centers for Senior Citizens Based on Disease and Nearest Locations using GPS - et. al., Gurram Sunitha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is not convenient nowadays for senior citizens to find an accessible and appropriate health care centre that can meet their needs. Therefore, this initiative helps senior citizens to look for a suitable facility depending on their location and their current illness. The scheme is simple and easily produces results. By using GPS feature or Internet network by using position coordinates and pre-built coordinate databases of nursing care facilities, the details of the nearest facility can be obtained along with the name of the location and buildings with smart phones. The software also provides a tracking service for consumers (senior citizens) so that, by forming a technical relationship with medical centres, it can offer a range of high-quality facilities. The contribution of this system is that through the O2O service, emergency responders can intelligently find a correct hospital that can treat the illness or accident of patients with a smart phone.